Assessment of brain-derived neurotrophic factor and osteopontin in a healthy pediatric population. (13th October 2018) - Chew, Joshua D; Markham, Larry; Smith, Holly M; Su, Yan Ru; Tomasek, Kelsey; Slaughter, James C; Sawyer, Douglas; Soslow, Jonathan H
Biomarkers are routinely used for noninvasive identification or monitoring of disease processes in clinical practice, as well as surrogate end points for drug development. There is a significant lack of data regarding biomarkers in children. An understanding of biomarker levels in a healthy pediatric cohort is essential as more studies begin to apply noninvasive biomarkers to pediatric populations. Brain-derived neurotrophic factor (BDNF) functions in neuronal survival and plasticity and is associated with exercise capacity and inflammatory disease processes. Osteopontin (OPN) plays a regulatory role in inflammation and may be a clinically useful biomarker of cardiovascular disease processes, ventricular remodeling, and skeletal muscle regeneration. This study describes our initial experience with a cohort of healthy pediatric patients and seeks to provide normal values of BDNF and OPN with correlation to age, gender, and cardiovascular and fitness measures. Serum BDNF and plasma OPN were measured using enzyme-linked immunosorbent assay in 33 healthy pediatric subjects. Subjects underwent complete cardiac evaluation, including echocardiography, exercise stress testing, and health risk assessment. The 5th–95th percentile was 5.63–37.86 ng/ml for serum BDNF and 4.9–164.9 ng/ml for plasma OPN. Plasma OPN correlated with number of days of exercise per week ( r = 0.46, p = 0.008). No other correlations were significant. This study provides the initial data on serum BDNF and plasma OPN in children and begins to explore the relationships of BDNF and OPN to cardiovascular health and fitness in the pediatric population.